TiO2 embedded in carbon submicron-tablets: synthesis from a metal–organic framework precursor and application as a superior anode in lithium-ion batteries1. Issue 57 (21st July 2015) - Wang, Peiyu; Lang, Junwei; Liu, Dongxia; Yan, Xingbin
<x xml:space="preserve">Abstract</x> A unique "blueberry muffin" structure provides the ideal anode characteristics of fast rechargeable LIBs, showing excellent long-term cycling stability.